Daily Herald, 24 January 1924 (1924)
1924 1918-1939 "Daily Herald, 24 January 1924" [T0281.jpg], 1924 The front page reports the first Labour Government and the death of Lenin. In 1924 the Conservative government was defeated in the House of Commons and Stanley Baldwin resigned. King George V called on the Labour leader, Ramsay MacDonald, as the leader of the next biggest party and the first Labour government was formed.